CD79B mutations in primary vitreoretinal lymphoma: Diagnostic and prognostic potential. (23rd November 2018) - Yonese, Ichiro; Takase, Hiroshi; Yoshimori, Mayumi; Onozawa, Erika; Tsuzura, Akiho; Miki, Tohru; Mochizuki, Manabu; Miura, Osamu; Arai, Ayako
Abstract: Objective: Primary vitreoretinal lymphoma (PVRL) is a rare type of lymphoma wherein the lesions are limited to the eyes. PVRL is difficult to diagnose because of the challenges related to obtaining sufficient samples for biopsy. Moreover, PVRL has poor outcomes and often leads to the development of central nervous system (CNS) lesions during its course. Two studies recently reported that approximately 70%‐80% of patients with vitreoretinal lymphoma have MYD88 L265P, which is frequently mutated in primary CNS lymphoma (PCNSL). PCNSL is closely associated with PVRL. The mutation of CD79B Y196 has been also frequently detected in PCNSL. Thus, we examined the mutation in PVRL to clarify its diagnostic and prognostic potential. Method: By using direct sequencing and allele‐specific polymerase chain reaction, we examined the mutation of CD79B Y196 and MYD88 L265P in the DNA extracted from the vitreous fluid of 17 patients with PVRL upon diagnosis. We also retrospectively analyzed their prognostic potential for PVRL. Results: Among the included patients, six patients (35%) were found with CD79B Y196 mutations. Twelve (71%) patients were positive for MYD88 L265P, and six samples from patients with benign uveitis were negative for both mutations. Interestingly, six patients with CD79B Y196 mutations developed CNS diseases significantly earlier (16.5 months) than 11 patients with CD79B WT (67 months; P  = 0.0135). Conclusion: Detecting CD79B Y196 in vitreous DNA may contribute to the confirmation of the diagnosis and may have a prognostic potential for patients with PVRL.